Art therapy with people diagnosed with psychosis: therapists' experiences of their work and the journey to their current practice. Issue 4 (2nd October 2021) - Holttum, Sue; Wright, Tim; Wood, Chris
ABSTRACT: Background: There was insufficient understanding of how art therapists experience their work with people with psychosis-related diagnoses, and of their practice development. Aims: To understand art therapists' perceived practise and its development regarding psychosis. Methods: Within a grounded theory framework, interviews and a focus group carried out in the years 2015–2017 elicited the experiences of 18 UK-based art therapists, working in a range of National Health Service (NHS) contexts, concerning art therapy in relation to psychosis and how they developed their current practice. Audio-recordings were transcribed verbatim and analysed to build theory. Results: The grounded theory proposes how practice and its development intertwine. Training confers resilience but therapists learn greatly from their clients, enhancing their ability for alliance-building. Therapists' early struggles also spur further training. Skills for trauma are helpful. Clients may become stuck or disengage, and/or develop through ongoing engagement with art and the art therapist, who supports their journey . The service and wider societal contexts impact the art therapist's work through their effect on clients and/or the art therapist's ability to attune to clients . Conclusions: The findings concur with previous research regarding common therapeutic factors, especially the alliance, and on other therapists' practice development. Implications for practice and research: Understanding therapy processes should incorporate service and societal influences on therapist and client. Training needs to include understanding adversity and trauma, and working with trauma. Plain-language summary: People who receive a diagnosis of psychosis or schizophrenia are sometimes offered art therapy. However, we did not know enough about exactly what art therapists do. It was also important to understand how art therapists come to know what helps people in art therapy. Art therapy training has to cover many things, not only psychosis, so art therapists learn their skills in various ways. Through interviews and a focus group we talked to 18 UK-based art therapists working in different NHS contexts and digitally recorded the discussions. We made written records of what was said, and analysed these to create a theory of how art therapists work with people who have been given a diagnosis of psychosis or schizophrenia across inpatient and outpatient settings. Our theory proposes that art therapists' training makes them quite resilient. However, they learn vital things from their clients. This especially helps them to become better at building a helpful relationship with each client. Some art therapists also seek further training when they are newly qualified, especially if they run into difficulties when trying to help a client. Some art therapists find it helpful to have skills for supporting people who have experienced past trauma. Clients develop through art-making and talking with the art therapist. Art therapists find it easier to do their work with clients if the service they work in is supportive. Our theory fits in with previous research, which says that building a good relationship with clients makes an important difference to the outcome in different kinds of therapies. Our theory also fits in with previous research on how other therapists develop their skills. Future research on art therapy should include looking at the service where the therapist works, and how it may affect both therapists and clients. Art therapy training needs to include trauma-related work. Abstract :